Pengembangan Panduan Praktikum Konsep Dasar Biologi dan Lingkungan Berbasis Project Based Learning - Faizal; Hendra Budiono (Jurnal Gentala Pendidikan Dasar, 2021)
The purpose of learning activities in the basic concepts of biologyand the environment can be achieved, a practical guide is neededthat can facilitate students in understanding the conceptscontained in the Course Learning Outcomes. This study aims toproduce a practical guide to the basic concepts of biology andproject-based environment-based learning that is valid andpractical to use in the lecture process. This research is a type ofresearch and development with the ADDIE development model(Analysis, Design, Development, Implementation, andEvaluation). The results showed that the practical guide to thebasic concepts of biology and the environment based on thelearning project that was developed met the media validity levelwith an average of 4.1 valid categories and material validity withan average of 4.2 valid categories. The lecturer's response showedthat the practical guide to the basic concepts of biology and theenvironment based on project based learning was in the practicalcategory with an average of 3.8 and student responses showedthat it was very practical to use with an average response of 4.4. Itcan be said that this research produces a practical guide that meetsthe level of validity and practicality.